On the Future of Public Policy Schools: What Can Be Done to 'Take Back Control'?. Issue 1 (27th February 2019) - Offe, Claus
Abstract : Anheier's five recommendations suggest valuable steps in the right direction. Yet let me add a sixth one – the comparative institutional analysis of what I have termed 'agency gaps', or structural governance deficiencies and 'hindrances'.